Risk factors and impact of hypertriglyceridemia in preterm infants under 32 weeks of gestation: optimizing intravenous lipid emulsion infusion rates–a single center retrospective study - Suh, Yoong-A; Park, Ji Hyun; Park, Bumhee; Choi, Seoheui; Park, Moon Sung; Lee, Jang Hoon (Frontiers in Pediatrics, 2025)
IntroductionIntravenous lipid emulsions are essential for parenteral nutrition in preterm infants. However, hypertriglyceridemia (HTG) is a common complication that can lead to severe complications if left untreated. This study analyzed factors influencing HTG and the effects of reduced intravenous lipid emulsion dosages.MethodsA retrospective cohort study involving premature infants born at less than 32 weeks of gestation and admitted to Ajou University Hospital between 2017 and 2022 was conducted. Infants with documented triglyceride levels within the first 10 days of life were included. The risk factors for HTG and the time to normalize triglyceride levels after intravenous lipid dose reduction were evaluated.ResultsHTG was diagnosed in 104 infants. Significant risk factors included lower birth weight (OR = 0.75; 95% CI, 0.66–0.85; p < 0.001), treated for patent ductus arteriosus (OR = 2.47; 95% CI, 1.30–4.69; p = 0.006), intravenous lipid emulsion intake (OR = 1.79; 95% CI, 1.25–2.55; p = 0.001), and serum glucose level (OR = 1.01; 95% CI, 1.00–1.02; p = 0.023). The average triglyceride level in the HTG group was 287.8 mg/dl, with intravenous lipid doses of 2.7 g/kg/day. Reducing intravenous lipid doses by 0.27 ± 0.46 g/kg/day shortened the triglyceride normalization time to 4.9 ± 5.0 days and reduced the risk of retinopathy of prematurity stage 2 or higher (OR = 0.59; 95% CI, 0.40–0.88; p = 0.011). The fat overload infusion rate, which induces HTG, was 0.332 cc/kg/h (1.6 g/kg/day).DiscussionLower birth weight, treated patent ductus arteriosus, serum glucose levels, and higher intravenous lipid levels are significant risk factors for HTG. Adjusting the lipid dose aids in triglyceride normalization and reducing severe retinopathy of prematurity risk. Careful monitoring and management of intravenous lipid emulsion infusion rates are crucial to prevent HTG.